Cross‐sectional relationships between dietary fat intake and serum cholesterol fatty acids in a Swedish cohort of 60‐year‐old men and women. Issue 3 (12th August 2015) - Laguzzi, F.; Alsharari, Z.; Risérus, U.; Vikström, M.; Sjögren, P.; Gigante, B.; Hellénius, M.‐L.; Cederholm, T.; Bottai, M.; de Faire, U.; Leander, K.
Abstract: Background: The present study aimed to describe the relationship between self‐reported dietary intake and serum cholesterol fatty acids (FAs) in a Swedish population of 60‐year‐old men and women. Methods: Cross‐sectional data collected in 1997–1998 from 4232 individuals residing in Stockholm County were used. Five diet scores were created to reflect the intake of saturated fats in general, as well as fats from dairy, fish, processed meat and vegetable oils and margarines. Gas chromatography was used to assess 13 FAs in serum cholesterol esters. The association between each diet score and specific FAs was assessed by percentile differences (PD) with 95% confidence intervals (CI) at the 10th, 25th, 50th, 75th and 90th percentile of each FA across levels of diet scores using quantile regression. Results: Fish intake was associated with high proportions of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). For each point increase in fish score, the 50th PD in EPA and DHA was 32.78% (95% CI = 29.22% to 36.35%) and 10.63% (95% CI = 9.52% to 11.74%), respectively. Vegetable fat intake was associated with a high proportion of linoleic acid and total polyunsaturated fatty acids (PUFA) and a low proportion of total saturated fatty acids (SFA). The intake of saturated fats in general and dairy fat was slightly associated with specific SFA, although the intake of fat from meat was not. Conclusions: In the present study population, using a rather simple dietary assessment method, the intake of fish and vegetable fats was clearly associated with serum PUFA, whereas foods rich in saturated fats in general showed a weak relationship with serum SFA. Our results may contribute to increased knowledge about underlying biology in diet–cardiovascular disease associations.